Effects of Diode, CO2, Er : YAG, and Er and Cr : YSGG on Titanium Implant Surfaces by Scanning Electron Microscopy - Amir Moeintaghavi; Hossein Bagheri; Mahdie Yavari Pour; Shervin Shafiei; Hamidreza Moslemi; Kamyar Abbasi; Behrad Rahbani Nobar; Amirreza Mehdizadeh; Farzaneh Ahrari; Mostafa Alam (Advances in Materials Science and Engineering)
This study aimed to determine the effects of various lasers on dental implants’ surface characteristics. Nine explanted dental implants were included. Two implants were randomly allocated to four intervention groups, namely, diode (2 W, 810 nm, 10 s), CO2 (2 W, 10600 nm, 10 s), Er : YAG (200 mJ/20 Hz, 2940 nm, 10 s), and Er, Cr : YSGG (200 mJ/20 Hz, 2780 nm, 10 s) groups and one control group. After laser irradiation, all implants were imaged with scanning electron microscopy. Qualitative changes on the surface of implants were evaluated. Quantitative surface changes at the threads and between the threads were assessed by software using depression and prominence plots. The paired t-test was used for statistical analysis. Diode laser irradiation showed the least surface changes while the Er : YAG group showed the greatest surface changes. Furthermore, CO2 and Er : YAG laser irradiation significantly altered the mean profile area at the threads (p<0.05), while CO2 and Er, Cr : YSGG laser irradiation significantly altered the mean profile area between the threads (p<0.05). Diode laser irradiation does not alter the implant surface characteristics. However, the use of CO2, Er : YAG, and Er, Cr : YSGG lasers on titanium implant surfaces is discouraged as they damage the titanium implant surfaces.